Determinant of Intangible Benefit and Cost in Integrated Biosystem Cattle in Yogyakarta - Kusumastuti, Tri Anggraeni; Nurtini, Sudi; Widiati, Rini; P. Syahlani, Suci; Muzayyanah, Mutjahidah Anggraini Ummul (2015)
Implementation of Rural Industries Research and Development Corporation (IRDC) through integrated farming with bio-cycle farming or integrated biosystem is very useful to increase the Total Economic Value. The objectives of the research was identify and measure the intangible value benefit and cost, calculate the Total Economic Value (TEV), and analyze the sensitivity of the farm business with the assumption that the change in maintenance management, pricing, and enviromental changes. Sampling was carried out on cattle farmers who are members diversification cattle and crop and organic vegetable and waste management into organic fertilizer. Measurement of intangible benefits and costs, Total Economic Value and senstivity were analyzed descriptively in table form. The results showed that the highest value of the intangible benefits derived from the use of manure that adds value to land productivity 6,196,500 IDR/head/year or 4,312,620 IDR/AU/year, Value Intangible Costs are Willingness To Accept (WTA) of 3,320,000 IDR/head/year, or 2,199, 500 IDR/AU/year higher than Willingness To Pay (WTP) of 456,765 IDR/head/year or 302,605 IDR/AU/year.The Total Economic Value of the assets showed that resource in village group system 237,548,645 IDR/head/year or 157,375,978 IDR/AU/year. An increasing number of cows population and improvement of the environment by offering individual system farmers willingness to relocate to the village group provides the highest TEV so that it can be concluded that the need for lingkages between economic and enviromental factors to increase the Total Economic Value.